Effect of a Collagen Membrane Combined With a Porous Titanium Membrane on Exophytic New Bone Formation in a Rabbit Calvarial Model. Issue 1 (1st January 2013) - Shin, Seung‐Il; Herr, Yeek; Kwon, Young‐Hyuk; Chung, Jong‐Hyuk
Abstract : Background: Previous studies showed that the use of a porous titanium membrane (TM) for exophytic bone regeneration does not effectively inhibit the infiltration of undesired tissue. Therefore, this study examines the effect of resorbable collagen membranes, such as cross‐linked type I collagen membrane (BA) and double‐layered porcine collagen membrane (BG), on the promotion of exophytic bone formation in guided bone regeneration when used in conjunction with a porous TM. Methods: Thirty‐six male New Zealand white rabbits were used in this study. Six rabbits were allotted to each test group. After decorticating the parietal bone, with or without filling the inner space with a freeze‐dried cortical bone allograft (OG), the collagen membranes were fixed with metal pins. The experimental groups were divided into the following six groups: TM only, TM + OG, TM + BA, TM + BG, TM + OG + BA, and TM + OG + BG. The experimental animals were sacrificed at 8 and 16 weeks after surgery. Non‐decalcified specimens were prepared and processed for histologic observations. The newly formed bone (percentage) was measured histomorphometrically. Results: BG combined with TM promoted new bone formation and maturation by inhibiting the infiltration of connective tissue. However, BA had no significant effect on new bone formation. The amount of new bone formation was higher at 16 weeks than at 8 weeks, but the difference was not significant. At 16 weeks, the best result for newly formed bone was with TM + OG + BG, with a significant difference from TM alone and TM + BA. Conclusions: Regardless of the use of graft materials, BG combined with TM promoted more bone formation than BA combined with TM or TM alone. Thus, using a commercial collagen membrane to cover a TM can promote new exophytic bone formation.